Pemilihan Paradigma Penelitian Akuntansi: Analisis Berdasarkan Pewarigaan dan Kecerdasan Manusia - Sriwinarti, Ni Ketut; Triyuwono, Iwan (Jurnal Akuntansi Multiparadigma, 2010)
The research aims to understand that pewarigaan, human intelligence and researcher behavior are determined by their choices and relation between behavior characteristic of researcher as well as their relation to philosophy of pewayangan actors (in this case Pandawa figures). The research has used phenomenology approach to interpret (a) informantsâ wewaran or pewarigaan (b) three intelligences owned by human being that most influence informantsâ choices (c) symbols that are most suitable with the behavior or character of the research subjects. Findings suggest that (a) the behavior forecasting according to pewarigaan resembles daily behavior of the informants, therefore pewarigaan can be used as one of alternatives to know the behavior of people (b) emerge anomalies between paradigms suggested in the pewarigaan with the chosen paradigm by informant, could be caused by preconceived thoughts of time, cost, and easiness in the research process. Other reasons were wills to avoid statistics or certain lecturer, and friendsâ/lecturersâ influence (c) firmness, focus and life harmony that is owned by positivism researcher is symbolized as Arjuna; wisdom and calmness of interpretive researcher is symbolized as Nakula-Sadewa; courage and firmness of critical researcher is symbolized as Bima, while freedom and intelligence of postmodernism researcher is symbolized as Yudhistira.